Taiwan [videorecording] where mountains meet the sea - Lin, Chia-ling-Publisher.; Meng, Fan-peng-Producer.; Wu, Martin-Director. (Taipei, Taiwan Kwang Hwa Mass Communications, 2005)
Taiwan-where mountain meet the sea, gives you a glimpse not only of Taiwan's natural features, but also lets you see the people's efforts and achievements. At the same time, we hope that through this modern. high-quality film, you come to appreciate Taiwan better than ever.
Wellington Wei / Taiwan Economic & Cultural Office (10-26-06)
Keywords: Taiwan